Corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fibers and preparation process

By modifying the treatment of graphene, nanozirconia and carbon fiber, the problem of thermal expansion and contraction of carbon fiber composite materials at high temperatures is solved, and the corrosion resistance and high temperature resistance of the material are significantly improved.

CN119507199APending Publication Date: 2025-02-25SUZHOU JINSHENG TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411430585.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Carbon fiber composites are prone to thermal expansion and contraction at high temperatures, resulting in stress accumulation and microcracks, which in turn affects its corrosion resistance and service life.

Method used

Graphene, nanozirconia and carbon fiber are modified and treated with gamma radiation and alkali solution to enhance the interface bonding force and thermal stability of the material to form a more stable protective layer.

Benefits of technology

It significantly improves the corrosion resistance and high temperature resistance of carbon fiber composites, extends its service life, and reduces the risk of structural damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119507199A_ABST
    Figure CN119507199A_ABST
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fibers and a preparation process, gamma radiation treatment and aqueous alkali treatment are used for promoting combination of graphene and zirconium oxide with carbon fibers, so that chemical stability and thermal stress stability of the graphene and the zirconium oxide on the carbon fibers are improved; the corrosion resistance and high temperature resistance of graphene and zirconium oxide can be brought to the carbon fiber, so that the carbon fiber has corrosion resistance and high temperature resistance, and the defects of insufficient corrosion resistance and high temperature resistance of a carbon fiber material in the prior art are overcome; gamma radiation treatment is carried out in an alkali solution, the interface bonding force between graphene and carbon fibers and a reinforcing compound or a matrix material can be enhanced, and compared with the prior art, the interface bonding force between graphene and carbon fibers and the matrix material can be enhanced; and a more stable protection layer is formed while the corrosion resistance of the graphene and the carbon fibers is improved, so that the material has excellent corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fiber product processing, in particular to a composite material processed with graphene, and in particular to a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber and a preparation process. Background Art

[0002] As a high-performance material, carbon fiber has extremely high specific strength and specific modulus, that is, its strength-to-density ratio and modulus-to-density ratio are very high, which makes it irreplaceable in situations requiring high temperature and high physical stability. Carbon fiber also has good corrosion resistance, fatigue resistance, good structural dimensional stability, good design, and can be formed in large areas. These characteristics provide a solid foundation for its application in many fields.

[0003] However, when carbon fiber is used as a high-strength component, the high strength causes the temperature of the carbon fiber to rise. The high temperature will cause thermal expansion of the carbon fiber composite material, and contraction will occur when cooled. This thermal expansion and contraction may cause stress inside the material, which in turn causes microcracks or structural damage, directly affecting the use of the carbon fiber. Microcracks and structural damage will make the carbon fiber susceptible to invasion by external corrosive substances, which will reduce the service life of the carbon fiber and reduce its safety.

[0004] Therefore, it is necessary to improve the method for preparing carbon fiber materials in the prior art to solve the above problems. Summary of the invention

[0005] The present invention overcomes the deficiencies of the prior art and provides a graphene / carbon fiber-based corrosion-resistant and high-temperature-resistant composite material and a preparation process thereof.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a preparation process of a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber, comprising the following steps:

[0007] S1: soaking the graphene powder and the carbon fiber in an alkaline solution for 1-2 hours respectively to obtain a first modified graphene powder and a first modified carbon fiber;

[0008] S2: treating the first modified graphene powder and the first modified carbon fiber in S1 with gamma radiation for 3-4 hours respectively to obtain second modified graphene powder and second modified carbon fiber;

[0009] S3: preparing a suspension of the secondary modified graphene powder, nano zirconium oxide powder and reinforcing compound solution in S2 to obtain a modified liquid;

[0010] S4: soaking the secondary modified carbon fiber in S2 in the modified liquid in S3 for 2-4 hours to obtain a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber.

[0011] In a preferred embodiment of the present invention, during the gamma radiation treatment process of S2, the primary modified graphene powder and the primary modified carbon fiber are located in the alkaline solution of S1.

[0012] In a preferred embodiment of the present invention, the radial dimension of the graphene powder in S1 is 2-12 μm, and the thickness dimension is 30-60 nm.

[0013] In a preferred embodiment of the present invention, the fineness of the carbon fiber in S1 is 5D-10D, and the carbon fiber is polyacrylonitrile-based carbon fiber.

[0014] In a preferred embodiment of the present invention, the alkaline solution in S1 is a mixed solution of aluminum hydroxide and sodium hydroxide, the mass of the aluminum hydroxide accounts for 10-15% of the mass of the alkaline solution, and the concentration of the alkaline solution is 20-35%.

[0015] In a preferred embodiment of the present invention, the dose of the gamma radiation treatment in S2 is 80-120 kGy, the once modified carbon fiber in S2 is stretched during the gamma radiation treatment, the stretching ratio is 120-140%, the stretching time lasts 5-10 minutes, and the interval between two adjacent stretchings is 30-40 minutes.

[0016] In a preferred embodiment of the present invention, the diameter of the nano zirconium oxide particles in S3 is 100-200 nm.

[0017] In a preferred embodiment of the present invention, the enhancing compound in S3 is one of fluoroalkyl phosphate, perfluorohexane and triphenyl phosphate, and the mass concentration of the enhancing compound solution is 15-20%.

[0018] In a preferred embodiment of the present invention, the mass ratio of the secondary modified graphene powder, the nano zirconium oxide powder and the reinforcing compound solution in S3 is 3-5:1-2:8-10.

[0019] To achieve the above-mentioned purpose, the second set of technical solutions adopted by the present invention is: a corrosion-resistant and high-temperature resistant composite material based on graphene / carbon fiber, which is prepared based on a preparation process of a corrosion-resistant and high-temperature resistant composite material based on graphene / carbon fiber.

[0020] The present invention solves the defects existing in the background technology and has the following beneficial effects:

[0021] (1) The present invention provides a preparation process of a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber, which uses gamma radiation treatment and alkaline solution treatment to promote the combination of graphene and zirconium oxide with carbon fiber, so that graphene and zirconium oxide have chemical stability and thermal stress stability on carbon fiber. Compared with the carbon fiber in the prior art, the corrosion resistance and high temperature resistance of graphene and zirconium oxide can be brought to carbon fiber, so that carbon fiber has corrosion resistance and high temperature resistance, which solves the defect of insufficient corrosion resistance and high temperature resistance of carbon fiber materials in the prior art.

[0022] (2) In the present invention, the alkaline solution is a mixture of aluminum hydroxide and sodium hydroxide. The aluminum hydroxide particles can be used as a dispersant. The mixture of aluminum hydroxide and sodium hydroxide can promote the hydroxylation of the graphene and carbon fiber surfaces and increase the surface activity. Compared with the prior art, the interfacial bonding force with the resin or other matrix materials is enhanced. The thermal stability of the aluminum molecules can improve the high temperature resistance of the material, so that the material has better corrosion resistance and high temperature resistance.

[0023] (3) In the present invention, during the gamma radiation treatment process, the first modified graphene powder and the first modified carbon fiber are located in an alkaline solution. The gamma radiation treatment in the alkaline solution can enhance the interfacial bonding force between the graphene and carbon fiber and the reinforcing compound or matrix material. Compared with the prior art, the interfacial bonding force between the graphene and carbon fiber and the matrix material can be enhanced, and a more stable protective layer can be formed while improving the corrosion resistance of the graphene and carbon fiber, so that the material has excellent corrosion resistance.

[0024] (4) In the present invention, the reinforcing compound is a fluoroalkyl phosphate, which has a low friction coefficient and can be used as a lubricant to reduce the friction inside the composite material. Compared with the prior art, it can maintain the stability of the internal structure of the material, avoid wear and tear that causes cracks and affects the density, and ensure the corrosion resistance and high temperature resistance of the material.

[0025] (5) In the present invention, secondary modified graphene powder, nano zirconium oxide powder and reinforcing compound solution are made into a suspension. The high specific surface area of ​​nano-scale zirconium oxide can increase the contact area with carbon fiber, thereby improving the bonding force of the interface compared with the prior art. The thermal expansion coefficient is based on the carbon fiber and the reinforcing compound, which helps to reduce thermal stress and improve the thermal stability of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 It is a method step diagram of a preferred embodiment of the present invention. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0030] like Figure 1 As shown, a preparation process of a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber comprises the following steps:

[0031] S1: Soak the graphene powder and carbon fiber in an alkaline solution for 1-2 hours to obtain primary modified graphene powder and primary modified carbon fiber. Soaking graphene and carbon fiber in an alkaline solution helps to remove surface impurities and oxides, while opening the surface structure of the material, increasing active sites, and creating conditions for subsequent chemical bonding and physical embedding.

[0032] The radial size of the graphene powder in S1 is 2-12μm and the thickness size is 30-60nm. Graphene has extremely high strength and toughness. By controlling the radial size of graphene, it can be ensured that it is evenly dispersed in the composite material, thereby improving the overall mechanical strength and toughness of the material on a macro scale. The smaller thickness size means that the graphene has a higher surface area. This increases the contact area between graphene and carbon fiber and other materials, which helps to improve the interfacial bonding force, thereby enhancing the overall performance of the composite material. The smaller thickness and larger radial size help graphene form a protective layer in the composite material, reducing the direct contact between carbon fiber and corrosive media, thereby improving the corrosion resistance of the composite material. Graphene has excellent thermal conductivity. By controlling its size, the thermal conduction path of graphene in the composite material can be optimized, thereby improving the thermal management capability of the composite material.

[0033] The fineness of the carbon fiber in S1 is 5D-10D, and the carbon fiber is polyacrylonitrile-based carbon fiber. Carbon fiber with moderate fineness can better combine with the matrix material to form a stronger interface, thereby improving the overall performance of the composite material.

[0034] The alkaline solution in S1 is a mixture of aluminum hydroxide and sodium hydroxide, the mass of aluminum hydroxide accounts for 10-15% of the mass of the alkaline solution, and the concentration of the alkaline solution is 20-35%. The addition of aluminum hydroxide helps to improve the dispersibility of graphene and carbon fiber in subsequent steps. Aluminum hydroxide particles can act as a dispersant to reduce the agglomeration between materials, thereby achieving a more uniform distribution in the composite material. The mixture of aluminum hydroxide and sodium hydroxide can promote the hydroxylation of the surface of graphene and carbon fiber, increase surface activity, and thus enhance the interfacial bonding with resin or other matrix materials. Aluminum hydroxide has good thermal stability and can remain stable during high temperature treatment, which helps to improve the thermal stability of the composite material.

[0035] S2: The primary modified graphene powder and the primary modified carbon fiber in S1 are treated with gamma radiation for 3-4 hours respectively to obtain secondary modified graphene powder and secondary modified carbon fiber; gamma radiation can further change the surface chemical properties of the material, increase the surface activity, and thus improve the corrosion resistance and high temperature resistance of the material. Radiation treatment may promote the cross-linking reaction inside the material and enhance the thermal stability and mechanical strength of the material.

[0036] During the gamma radiation treatment of S2, the first modified graphene powder and the first modified carbon fiber are located in the alkaline solution of S1. Gamma radiation can further activate the surface of graphene and carbon fiber in the alkaline solution environment, increase their chemical activity, and thus promote subsequent chemical bonding and uniform dispersion of the materials. Gamma radiation treatment in an alkaline solution can enhance the interfacial bonding between graphene and carbon fiber and reinforcing compounds or matrix materials, gamma radiation treatment can improve the corrosion resistance of graphene and carbon fiber, and the alkaline solution and gamma radiation treatment can act together on the surface of the material to form a more stable protective layer.

[0037] The dose of gamma radiation treatment in S2 is 80-120 kGy. The modified carbon fiber in S2 is stretched during the gamma radiation treatment, with a stretching ratio of 120-140%, a stretching time of 5-10 minutes, and an interval of 30-40 minutes between two adjacent stretchings. Stretching during the gamma radiation treatment can enhance the interfacial bonding between the carbon fiber and the matrix material. Stretching can promote microstructural changes on the surface of the carbon fiber and increase the contact area and bonding points with the matrix material. Gamma radiation treatment can improve the thermal stability of the carbon fiber, and the stretching operation can help further improve this stability. Stretching can promote the compaction of the internal structure of the carbon fiber and reduce the decrease in corrosion resistance caused by thermal expansion and contraction of the carbon fiber during heating.

[0038] S3: The secondary modified graphene powder, nano zirconium oxide powder and reinforcing compound solution in S2 are made into a suspension to obtain a modified liquid; nano zirconium oxide has excellent corrosion resistance, and its addition can significantly improve the corrosion resistance of the composite material, and zirconium oxide is a high temperature resistant material, and its addition helps to improve the stability of the composite material in a high temperature environment.

[0039] The diameter of nano zirconium oxide particles in S3 is 100-200nm. Nano-sized zirconium oxide particles have a high specific surface area, which helps them form a denser network structure in the composite material, thereby improving the mechanical strength of the composite material. The improvement of mechanical properties will improve the ability to resist corrosion and have better corrosion resistance.

[0040] The reinforcing compound in S3 is one of fluoroalkyl phosphate, perfluorohexane and triphenyl phosphate, and the mass concentration of the reinforcing compound solution is 15-20%. These compounds have a low friction coefficient and can be used as lubricants to reduce friction inside the composite material and improve its wear resistance and service life.

[0041] The mass ratio of the secondary modified graphene powder, nano zirconium oxide powder and reinforcing compound solution in S3 is 3-5:1-2:8-10. The appropriate mass ratio can enhance the interfacial bonding force between graphene, nano zirconium oxide and reinforcing compound, thereby improving the overall performance of the composite material. The secondary modified graphene powder, nano zirconium oxide powder and reinforcing compound solution are made into a suspension. The high specific surface area of ​​nano-scale zirconium oxide can increase the contact area with carbon fiber, thereby improving the interfacial bonding force, and the thermal expansion coefficient is based on the carbon fiber and the reinforcing compound, which helps to reduce thermal stress and improve the thermal stability of the composite material.

[0042] S4: Soak the secondary modified carbon fiber in S2 in the modified liquid in S3 for 2-4 hours to obtain a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber. By soaking the modified carbon fiber in the modified liquid containing graphene, nano zirconium oxide and reinforcing compounds, these materials can be evenly dispersed on the surface of the carbon fiber, thereby improving the overall performance of the composite material.

[0043] Gamma radiation treatment and alkaline solution treatment are used to promote the combination of graphene and zirconium oxide with carbon fiber, so that the chemical stability and thermal stress stability of graphene and zirconium oxide to carbon fiber can be brought to the corrosion resistance and high temperature resistance of graphene and zirconium oxide to carbon fiber, making carbon fiber corrosion-resistant and high-temperature-resistant, solving the defects of insufficient corrosion resistance and high-temperature resistance of carbon fiber materials in the prior art.

[0044] To achieve the above-mentioned purpose, the second set of technical solutions adopted by the present invention is: a corrosion-resistant and high-temperature resistant composite material based on graphene / carbon fiber, which is prepared based on a preparation process of a corrosion-resistant and high-temperature resistant composite material based on graphene / carbon fiber.

[0045] Embodiment 1

[0046] This embodiment prepares a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber, and the preparation process is as follows:

[0047] S1: immersing graphene powder with a radial size of 5 μm and a thickness of 40 nm and polyacrylonitrile-based carbon fiber with a fineness of 8D in a mixed solution of aluminum hydroxide and sodium hydroxide for 2 hours, respectively, the mass of aluminum hydroxide accounts for 10% of the mass of the mixed solution, and the concentration of the mixed solution is 25%, to obtain a primary modified graphene powder and a primary modified carbon fiber;

[0048] S2: The first modified graphene powder and the first modified carbon fiber in S1 are respectively subjected to gamma radiation treatment with a dose of 60 kGy for 3 hours. During the gamma radiation treatment, the first modified graphene powder and the first modified carbon fiber are located in a mixed solution of aluminum hydroxide and sodium hydroxide in S1. The first modified carbon fiber is stretched during the gamma radiation treatment, with a stretching ratio of 120% and a stretching time of 10 minutes. The interval between two adjacent stretches is 30 minutes, thereby obtaining a second modified graphene powder and a second modified carbon fiber;

[0049] S3: preparing a suspension of the secondary modified graphene powder in S2, nano zirconium oxide powder with a particle diameter of 150 nm, and a 15% concentration of a fluoroalkyl phosphate solution, wherein the mass ratio of the secondary modified graphene powder, the nano zirconium oxide powder, and the fluoroalkyl phosphate solution is 4:1:8, to obtain a modified liquid;

[0050] S4: Soak the secondary modified carbon fiber in S2 in the modified liquid in S3 for 3 hours to obtain a corrosion-resistant and high-temperature resistant composite material based on graphene / carbon fiber.

[0051] Embodiment 2

[0052] This embodiment prepares a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber, and the preparation process is as follows:

[0053] S1: immersing graphene powder with a radial size of 5 μm and a thickness of 40 nm and polyacrylonitrile-based carbon fiber with a fineness of 8D in a mixed solution of aluminum hydroxide and sodium hydroxide for 2 hours, respectively, the mass of aluminum hydroxide accounts for 10% of the mass of the mixed solution, and the concentration of the mixed solution is 25%, to obtain a primary modified graphene powder and a primary modified carbon fiber;

[0054] S2: The first modified graphene powder and the first modified carbon fiber in S1 are respectively subjected to gamma radiation treatment with a dose of 80 kGy for 3 hours. During the gamma radiation treatment, the first modified graphene powder and the first modified carbon fiber are located in a mixed solution of aluminum hydroxide and sodium hydroxide in S1. The first modified carbon fiber is stretched during the gamma radiation treatment, with a stretching ratio of 120% and a stretching time of 10 minutes. The interval between two adjacent stretches is 30 minutes, thereby obtaining a second modified graphene powder and a second modified carbon fiber;

[0055] S3: preparing a suspension of the secondary modified graphene powder in S2, nano zirconium oxide powder with a particle diameter of 150 nm, and a 15% concentration of a fluoroalkyl phosphate solution, wherein the mass ratio of the secondary modified graphene powder, the nano zirconium oxide powder, and the fluoroalkyl phosphate solution is 4:1:8, to obtain a modified liquid;

[0056] S4: Soak the secondary modified carbon fiber in S2 in the modified liquid in S3 for 3 hours to obtain a corrosion-resistant and high-temperature resistant composite material based on graphene / carbon fiber.

[0057] Embodiment 3

[0058] This embodiment prepares a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber, and the preparation process is as follows:

[0059] S1: immersing graphene powder with a radial size of 5 μm and a thickness of 40 nm and polyacrylonitrile-based carbon fiber with a fineness of 8D in a mixed solution of aluminum hydroxide and sodium hydroxide for 2 hours, respectively, the mass of aluminum hydroxide accounts for 10% of the mass of the mixed solution, and the concentration of the mixed solution is 25%, to obtain a primary modified graphene powder and a primary modified carbon fiber;

[0060] S2: The first modified graphene powder and the first modified carbon fiber in S1 are respectively subjected to gamma radiation treatment with a dose of 100 kGy for 3 hours. During the gamma radiation treatment, the first modified graphene powder and the first modified carbon fiber are located in a mixed solution of aluminum hydroxide and sodium hydroxide in S1. The first modified carbon fiber is stretched during the gamma radiation treatment, with a stretching ratio of 120% and a stretching time of 10 minutes. The interval between two adjacent stretchings is 30 minutes, thereby obtaining a second modified graphene powder and a second modified carbon fiber;

[0061] S3: preparing a suspension of the secondary modified graphene powder in S2, nano zirconium oxide powder with a particle diameter of 150 nm, and a 15% concentration of a fluoroalkyl phosphate solution, wherein the mass ratio of the secondary modified graphene powder, the nano zirconium oxide powder, and the fluoroalkyl phosphate solution is 4:1:8, to obtain a modified liquid;

[0062] S4: Soak the secondary modified carbon fiber in S2 in the modified liquid in S3 for 3 hours to obtain a corrosion-resistant and high-temperature resistant composite material based on graphene / carbon fiber.

[0063] Embodiment 4

[0064] This embodiment prepares a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber, and the preparation process is as follows:

[0065] S1: immersing graphene powder with a radial size of 5 μm and a thickness of 40 nm and polyacrylonitrile-based carbon fiber with a fineness of 8D in a mixed solution of aluminum hydroxide and sodium hydroxide for 2 hours, respectively, the mass of aluminum hydroxide accounts for 10% of the mass of the mixed solution, and the concentration of the mixed solution is 25%, to obtain a primary modified graphene powder and a primary modified carbon fiber;

[0066] S2: The first modified graphene powder and the first modified carbon fiber in S1 are respectively subjected to gamma radiation treatment with a dose of 120 kGy for 3 hours. During the gamma radiation treatment, the first modified graphene powder and the first modified carbon fiber are located in a mixed solution of aluminum hydroxide and sodium hydroxide in S1. The first modified carbon fiber is stretched during the gamma radiation treatment, with a stretching ratio of 120%, a stretching time of 10 minutes, and an interval of 30 minutes between two adjacent stretches, to obtain a second modified graphene powder and a second modified carbon fiber;

[0067] S3: preparing a suspension of the secondary modified graphene powder in S2, nano zirconium oxide powder with a particle diameter of 150 nm, and a 15% concentration of a fluoroalkyl phosphate solution, wherein the mass ratio of the secondary modified graphene powder, the nano zirconium oxide powder, and the fluoroalkyl phosphate solution is 4:1:8, to obtain a modified liquid;

[0068] S4: Soak the secondary modified carbon fiber in S2 in the modified liquid in S3 for 3 hours to obtain a corrosion-resistant and high-temperature resistant composite material based on graphene / carbon fiber.

[0069] Embodiment 5

[0070] This embodiment prepares a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber, and the preparation process is as follows:

[0071] S1: immersing graphene powder with a radial size of 5 μm and a thickness of 40 nm and polyacrylonitrile-based carbon fiber with a fineness of 8D in a mixed solution of aluminum hydroxide and sodium hydroxide for 2 hours, respectively, the mass of aluminum hydroxide accounts for 10% of the mass of the mixed solution, and the concentration of the mixed solution is 25%, to obtain a primary modified graphene powder and a primary modified carbon fiber;

[0072] S2: The first modified graphene powder and the first modified carbon fiber in S1 are respectively subjected to gamma radiation treatment with a dose of 140 kGy for 3 hours. During the gamma radiation treatment, the first modified graphene powder and the first modified carbon fiber are located in a mixed solution of aluminum hydroxide and sodium hydroxide in S1. The first modified carbon fiber is stretched during the gamma radiation treatment, with a stretching ratio of 120%, a stretching time of 10 minutes, and an interval of 30 minutes between two adjacent stretches, to obtain a second modified graphene powder and a second modified carbon fiber;

[0073] S3: preparing a suspension of the secondary modified graphene powder in S2, nano zirconium oxide powder with a particle diameter of 150 nm, and a 15% concentration of a fluoroalkyl phosphate solution, wherein the mass ratio of the secondary modified graphene powder, the nano zirconium oxide powder, and the fluoroalkyl phosphate solution is 4:1:8, to obtain a modified liquid;

[0074] S4: Soak the secondary modified carbon fiber in S2 in the modified liquid in S3 for 3 hours to obtain a corrosion-resistant and high-temperature resistant composite material based on graphene / carbon fiber.

[0075] Embodiment 6

[0076] This embodiment prepares a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber, and the preparation process is as follows:

[0077] S1: immersing graphene powder with a radial size of 5 μm and a thickness of 40 nm and polyacrylonitrile-based carbon fiber with a fineness of 8D in a mixed solution of aluminum hydroxide and sodium hydroxide for 2 hours, respectively, the mass of aluminum hydroxide accounts for 10% of the mass of the mixed solution, and the concentration of the mixed solution is 25%, to obtain a primary modified graphene powder and a primary modified carbon fiber;

[0078] S2: The first modified graphene powder and the first modified carbon fiber in S1 are respectively subjected to gamma radiation treatment with a dose of 100 kGy for 3 hours. During the gamma radiation treatment, the first modified graphene powder and the first modified carbon fiber are located in a mixed solution of aluminum hydroxide and sodium hydroxide in S1. The first modified carbon fiber is stretched during the gamma radiation treatment, with a stretching ratio of 120% and a stretching time of 10 minutes. The interval between two adjacent stretchings is 30 minutes, thereby obtaining a second modified graphene powder and a second modified carbon fiber;

[0079] S3: preparing a suspension of the secondary modified graphene powder in S2, nano zirconium oxide powder with a particle diameter of 150 nm, and a 15% concentration of a fluoroalkyl phosphate solution, wherein the mass ratio of the secondary modified graphene powder, the nano zirconium oxide powder, and the fluoroalkyl phosphate solution is 4:1:7, to obtain a modified liquid;

[0080] S4: Soak the secondary modified carbon fiber in S2 in the modified liquid in S3 for 3 hours to obtain a corrosion-resistant and high-temperature resistant composite material based on graphene / carbon fiber.

[0081] Embodiment 7

[0082] This embodiment prepares a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber, and the preparation process is as follows:

[0083] S1: immersing graphene powder with a radial size of 5 μm and a thickness of 40 nm and polyacrylonitrile-based carbon fiber with a fineness of 8D in a mixed solution of aluminum hydroxide and sodium hydroxide for 2 hours, respectively, the mass of aluminum hydroxide accounts for 10% of the mass of the mixed solution, and the concentration of the mixed solution is 25%, to obtain a primary modified graphene powder and a primary modified carbon fiber;

[0084] S2: The first modified graphene powder and the first modified carbon fiber in S1 are respectively subjected to gamma radiation treatment with a dose of 100 kGy for 3 hours. During the gamma radiation treatment, the first modified graphene powder and the first modified carbon fiber are located in a mixed solution of aluminum hydroxide and sodium hydroxide in S1. The first modified carbon fiber is stretched during the gamma radiation treatment, with a stretching ratio of 120% and a stretching time of 10 minutes. The interval between two adjacent stretchings is 30 minutes, thereby obtaining a second modified graphene powder and a second modified carbon fiber;

[0085] S3: preparing a suspension of the secondary modified graphene powder in S2, nano zirconium oxide powder with a particle diameter of 150 nm, and a 15% concentration of a fluoroalkyl phosphate solution, wherein the mass ratio of the secondary modified graphene powder, the nano zirconium oxide powder, and the fluoroalkyl phosphate solution is 4:1:9, to obtain a modified liquid;

[0086] S4: Soak the secondary modified carbon fiber in S2 in the modified liquid in S3 for 3 hours to obtain a corrosion-resistant and high-temperature resistant composite material based on graphene / carbon fiber.

[0087] Embodiment 8

[0088] This embodiment prepares a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber, and the preparation process is as follows:

[0089] S1: immersing graphene powder with a radial size of 5 μm and a thickness of 40 nm and polyacrylonitrile-based carbon fiber with a fineness of 8D in a mixed solution of aluminum hydroxide and sodium hydroxide for 2 hours, respectively, the mass of aluminum hydroxide accounts for 10% of the mass of the mixed solution, and the concentration of the mixed solution is 25%, to obtain a primary modified graphene powder and a primary modified carbon fiber;

[0090] S2: The first modified graphene powder and the first modified carbon fiber in S1 are respectively subjected to gamma radiation treatment with a dose of 100 kGy for 3 hours. During the gamma radiation treatment, the first modified graphene powder and the first modified carbon fiber are located in a mixed solution of aluminum hydroxide and sodium hydroxide in S1. The first modified carbon fiber is stretched during the gamma radiation treatment, with a stretching ratio of 120% and a stretching time of 10 minutes. The interval between two adjacent stretchings is 30 minutes, thereby obtaining a second modified graphene powder and a second modified carbon fiber;

[0091] S3: preparing a suspension of the secondary modified graphene powder in S2, nano zirconium oxide powder with a particle diameter of 150 nm, and a 15% concentration of a fluoroalkyl phosphate solution, wherein the mass ratio of the secondary modified graphene powder, the nano zirconium oxide powder, and the fluoroalkyl phosphate solution is 4:1:10, to obtain a modified liquid;

[0092] S4: Soak the secondary modified carbon fiber in S2 in the modified liquid in S3 for 3 hours to obtain a corrosion-resistant and high-temperature resistant composite material based on graphene / carbon fiber.

[0093] Embodiment 9

[0094] This embodiment prepares a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber, and the preparation process is as follows:

[0095] S1: immersing graphene powder with a radial size of 5 μm and a thickness of 40 nm and polyacrylonitrile-based carbon fiber with a fineness of 8D in a mixed solution of aluminum hydroxide and sodium hydroxide for 2 hours, respectively, the mass of aluminum hydroxide accounts for 10% of the mass of the mixed solution, and the concentration of the mixed solution is 25%, to obtain a primary modified graphene powder and a primary modified carbon fiber;

[0096] S2: The first modified graphene powder and the first modified carbon fiber in S1 are respectively subjected to gamma radiation treatment with a dose of 100 kGy for 3 hours. During the gamma radiation treatment, the first modified graphene powder and the first modified carbon fiber are located in a mixed solution of aluminum hydroxide and sodium hydroxide in S1. The first modified carbon fiber is stretched during the gamma radiation treatment, with a stretching ratio of 120% and a stretching time of 10 minutes. The interval between two adjacent stretchings is 30 minutes, thereby obtaining a second modified graphene powder and a second modified carbon fiber;

[0097] S3: preparing a suspension of the secondary modified graphene powder in S2, nano zirconium oxide powder with a particle diameter of 150 nm, and a 15% concentration of a fluoroalkyl phosphate solution, wherein the mass ratio of the secondary modified graphene powder, the nano zirconium oxide powder, and the fluoroalkyl phosphate solution is 4:1:11, to obtain a modified liquid;

[0098] S4: Soak the secondary modified carbon fiber in S2 in the modified liquid in S3 for 3 hours to obtain a corrosion-resistant and high-temperature resistant composite material based on graphene / carbon fiber.

[0099] Comparative Example 1

[0100] This comparative example prepares a carbon fiber material, and the preparation process is as follows:

[0101] S1: preparing a suspension of graphene powder with a radial size of 5 μm and a thickness of 40 nm, nano zirconium oxide powder with a diameter of 150 nm, and water in a ratio of 4:1:11;

[0102] S2: Soaking polyacrylonitrile-based carbon fiber with a fineness of 8D in the suspension for 3 hours to obtain a carbon fiber material.

[0103] Take samples of equal weight from Examples 1 to 9 and Comparative Example 1, place them in an oven and heat them to 150°C, and measure the shear strength of the samples. After soaking the samples in dilute hydrochloric acid with a pH of 3 for 500 hours, measure the tensile strength of the samples according to the national standard GB / T1040-92 and calculate the tensile strength retention rate. The test data are shown in Table 1.

[0104] Table 1 Experimental data of Examples 1 to 9 and Comparative Example 1

[0105]

[0106]

[0107] It can be seen from Table 1 that the shear strength and tensile strength retention rates in Examples 1 to 9 are greater than the shear strength and tensile strength retention rates in Comparative Example 1. The corrosion-resistant and high-temperature resistant composite material based on graphene / carbon fiber in the present application has significant advantages.

[0108] In Examples 1 to 5, as the gamma radiation dose increases, the shear strength and tensile strength retention first increase and then decrease. This is because radiation can promote cross-linking between polymer chains to form a tighter network structure, thereby improving the shear strength and tensile strength retention rate. Gamma radiation can generate free radicals, which can participate in the polymerization reaction of the material, but excessive free radicals lead to excessive degradation of the material, thereby reducing the shear strength and tensile strength retention rate. The preferred embodiment is Example 3.

[0109] In Example 3 and Examples 6 to 9, as the mass ratio of the fluoroalkyl phosphate solution in the suspension gradually increases, the shear strength and tensile strength retention first increase and then decrease, which is because the fluoroalkyl phosphate may help improve the interface bonding between the matrix and the reinforcing material. The enhanced interface bonding can improve the stress transfer efficiency, thereby increasing the shear and tensile strength retention rate of the composite material, but when the mass ratio of the fluoroalkyl phosphate increases to a certain extent, excessive plasticization may occur, resulting in weakened interactions between polymer chains and decreased cohesion of the material, thereby reducing the shear and tensile strength retention rate. The preferred embodiment is Example 7.

[0110] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.

Claims

1. A preparation process of a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber, characterized in that: The following steps are involved: S1: soaking the graphene powder and the carbon fiber in an alkaline solution for 1-2 hours respectively to obtain a first modified graphene powder and a first modified carbon fiber; S2: treating the first modified graphene powder and the first modified carbon fiber in S1 with gamma radiation for 3-4 hours respectively to obtain second modified graphene powder and second modified carbon fiber; S3: preparing a suspension of the secondary modified graphene powder, nano zirconium oxide powder and reinforcing compound solution in S2 to obtain a modified liquid; S4: soaking the secondary modified carbon fiber in S2 in the modified liquid in S3 for 2-4 hours to obtain a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber.

2. The preparation process of a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber according to claim 1, characterized in that: During the gamma radiation treatment of S2, the first modified graphene powder and the first modified carbon fiber are located in the alkaline solution of S1.

3. The preparation process of a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber according to claim 1, characterized in that: The graphene powder in S1 has a radial dimension of 2-12 μm and a thickness of 30-60 nm.

4. The preparation process of a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber according to claim 1, characterized in that: The fineness of the carbon fiber in S1 is 5D-10D, and the carbon fiber is polyacrylonitrile-based carbon fiber.

5. The preparation process of the corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber according to claim 1, characterized in that: The alkaline solution in S1 is a mixed solution of aluminum hydroxide and sodium hydroxide, the mass of the aluminum hydroxide accounts for 10-15% of the mass of the alkaline solution, and the concentration of the alkaline solution is 20-35%.

6. The preparation process of the corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber according to claim 1, characterized in that: The dosage of the gamma radiation treatment in S2 is 80-120 kGy, and the primary modified carbon fiber in S2 is stretched during the gamma radiation treatment, with a stretching ratio of 120-140%, a stretching duration of 5-10 minutes, and an interval of 30-40 minutes between two adjacent stretchings.

7. The preparation process of a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber according to claim 1, characterized in that: The diameter of the nano zirconium oxide particles in S3 is 100-200 nm.

8. The preparation process of the corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber according to claim 1, characterized in that: The enhancing compound in S3 is one of fluoroalkyl phosphate, perfluorohexane and triphenyl phosphate, and the mass concentration of the enhancing compound solution is 15-20%.

9. The preparation process of the corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber according to claim 1, characterized in that: The mass ratio of the secondary modified graphene powder, the nano zirconium oxide powder and the reinforcing compound solution in S3 is 3-5:1-2:8-10.

10. A corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber, characterized in that: It is prepared by a preparation process of a corrosion-resistant and high-temperature-resistant composite material based on graphene / carbon fiber according to any one of claims 1-9.